SUNAT PEREMPUAN DALAM PERSPEKTIF FIKIH - Afifi Fauzi Abbas; Mona Eliza (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
In 2008 the MUI issued a fatwa related to female circumcision, namely fatwa number 94